THE PHENOMENON OF ONLINE GAMBLING UNDER THE GUISE OF ONLINE GAMES AMONG COLLEGE STUDENT - Abdul Azis Lubis; Syarbaini Saleh; Yummi Jumiati Marsa (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
This study aims to find out: The Phenomenon of Online Gambling Clucking Online Games Among Students in Pasar V Tembung Village. The research method used in this thesis is a type of qualitative research using the phenomenology method. The data collection technique used was various data obtained from observations, interviews, and documentation at market V in Tembung Village. The results of this study indicate that the phenomenon of online gambling under the guise of online games among students is that many students are familiar with online gambling in their free time and because there is no activity either on campus, at boarding houses or at home. Online gamblers utilize information and communication technology as a means of modern gambling, making it more profitable for online gamblers because it does not require them to meet in person. The forms are: Slots, Togel, Links, Websites, Poker, Rummy, Football Gambling and Higgs Domino. Where teenagers do online gambling as a form of activity in the process of fulfilling their needs, both psychological and material. The resulting impact affects themselves personally and others, both having a negative impact on academic achievement, the economy, psychology, time and resulting in criminal acts.